Poor Health and Loneliness in Later Life: The Role of Depressive Symptoms, Social Resources, and Rural Environments - Vanessa Burholt (The Journals of Gerontology Series B: Psychological Sciences and Social Sciences, 2014)
OBJECTIVES: We draw on cognitive discrepancy theory to hypothesize and test a pathway from poor health to loneliness in later life. We hypothesize that poor health will have a negative influence on social participation and social resources, and these factors will mediate between health and loneliness. We hypothesize that rural environments will amplify any difficulties associated with social participation or accessing social resources and that depression will moderate how intensely people react to levels of social contact and support.METHODS: We conceptualize a mediation model and a moderated-mediation model. Nationally representative data on older people living in the Republic of Ireland are used to validate the hypothesized pathways.RESULTS: In the mediation model, health has a significant indirect effect on loneliness through the mediating variables social resources and social participation. In the moderated-mediation model, rurality moderates the pathway between health and social resources but not social participation. Depressive symptoms moderate the effect of social resources on loneliness but not social participation.DISCUSSION: The results provide further credence to cognitive discrepancy theory, suggesting that depressive symptoms influence cognitive processes, interfering with judgments about the adequacy of social interaction. The theory is extended by demonstrating the impact of the environment on loneliness.